Enhancing cancer care with improved checkpoint inhibitors - Vickram A S; Saghya Infant Shofia; A. Saravaran; Vidhya Lakshmi Sivakumar; Packiyam Thamarai; Manikandan Sivasubramanian; Shivani Chopra; Hitesh Chopra (EXCLI Journal : Experimental and Clinical Sciences)
The emergence of checkpoint inhibitors targeting the PD-1/PD-L1 axis marks a paradigm shift in cancer therapy, offering a novel avenue for enhancing patient outcomes. This review examines the structural and functional dynamics of PD-1 and PD-L1 while exploring the clinical implications of current PD-1/PD-L1 monoclonal antibodies. Highlighting recent advancements, this paper delves into the promising results from combination therapies that present a multifaceted attack on tumor progression. Despite the success observed across various cancer types, challenges such as immune resistance remain. Future considerations are discussed with an emphasis on the need for further clinical studies, aiming to refine and broaden the curative potential of PD-1/PD-L1 inhibitors in oncology. This review postulates that ongoing research and innovative approaches could significantly enhance cancer care, making immunotherapy an even more central strategy in the fight against cancer.